Sport policy in China (Mainland) - Zheng, J.; Chen, S.; Tan, T.-C.; Lau, P. W. C. (International Journal of Sport Policy and Politics, 2018)
Sport has been an integral part of the Chinese government`s policy agenda since the People`s Republic of China was founded in 1949. The policy prominence of sport has been further elevated in the last two to three decades, as indicated by the steady increase in elite sport success, the hosting of sports events such as the Olympic Games, China`s increased global engagement with sport organisations and the developments in sport professionalisation and commercialisation. This article reviews China`s sport policy at different periods since its inception, analyses the rationale for, and form and extent of, government intervention, presents the sport structure in China and identifies the dominant characteristics of its sport policy. In addition, various sport policy areas, ranging from elite sport and mass sport to sports mega-events, and sports professionalisation are discussed, and their relative policy significances are compared. The degree of balance between these areas and policy priorities are thus defined. Finally, emerging trends and issues are introduced. Abstract from author